Christianity and Social Order as a model of collaborative leadership in the public arena - Spencer, Stephen (Theology, 2022)
Placing Christianity and Social Order within a wider movement that began with the Malvern Conference in 1941 and continued with a series of mass meetings after it was published, and noting the way its content drew together and promoted various strands of Christian social reflection, this article highlights the ecumenical and collaborative nature of the leadership it provided.